URDU RESEARCH: ASPECTS AND PROSPECTS - Iqbal, Shamaila; Hamid, Dr. Muhammad (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The tradition of Urdu literary research goes back to the writing of Tazkiras. The first Tazkira was written in 1752. It was followed by a stream of Tazkira writing. In the next phase Sir Syed and his companions introduced modern style of research. Afterwards objective scientific style of literary research was introduced by Hafiz Mehmood Shirani on the break of 20th century. Henceforward, Urdu research went on the pace and reached at the edge of 21st century. During this journey it saw many changes. In the beginning, most of the works were past-oriented. While in the last 50 years, it has turned towards future. Now both of the streams are going side by side and focus is going to shift towards futurization.